Hubungan Gaya Belajar dan Motivasi Belajar terhadap Hasil Belajar Secara Daring pada Mata Pelajaran Teknologi Layanan Jaringan di SMK PGRI 1 Kota Pasuruan - Mukhamad Naufal Ar-Rozaq; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The research was carried out at SMK PGRI 1 Pasuruan City with the number of respondents being 21 students of class XI TKJ and 19 students of class XII TKJ. The purpose of the study was to find out the hypothesis of the relationship between learning styles and learning motivation with learning outcomes for the subjects of Network Service Technology for class XI and XII students of TKJ SMK PGRI 1 Pasuruan City during the online learning period during the Covid 19 period by using quantitative methods. The results of the study were partially divided into 2 independent variables, namely the results of the analysis of the relationship between learning styles and student learning outcomes and the relationship between learning motivation and student learning outcomes. Simultaneous research results consist of the results of the analysis of the relationship between learning styles and learning motivation on student learning outcomes.